Planejamento de experimentos bayesianos: aplicações em experimentos na presença de tendências lineares - Lima, Luis Gustavo Guedes Bessa (Universidade Federal de São Carlos, 2007)
We present a general introduction in the construction of experimental design, spe- cially a general factorial design and factorial design 2k and some Bayesian criteria in the construction of experimental design. In practice, usually the researcher can have a priori knowledge of specialists for estimated quantities from an experiment. The use of Bayesian methods can take on best results with low costs. Many Bayesian criteria in- troduced in literature are presented. One of the main applications in the experimental design construction involve the existance of linear trends with objective of verifying the best sequence of runs, specially the factorial designs with eight runs. In this disertation, we introduce some basic concepts in design of experiments and the use of the Bayesian approach to have more e¢ cient and less cost experiments. The main goal of the work, is to consider a special case of great importance in applied indistrial work: the presence of linear trend. In this case, we present a comparative study in design of experiments under the classical and Bayesian approaches.
Keywords: Estatística; Planejamento experimental; Planejamento fatorial; Método bayesiano; Densidades preditivas; Tendências lineares; Experimental design; Factorial designs; Bayesian criteria; Utility func-tions; Predictive densities; Linear trends; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA